1999
DOI: 10.1136/hrt.81.5.523
|View full text |Cite
|
Sign up to set email alerts
|

Low dose dobutamine stress echocardiography predicts the improvement of left ventricular systolic function in dilated cardiomyopathy

Abstract: (Heart 1999;81:523-527)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 19 publications
2
32
0
1
Order By: Relevance
“…Foi determinada a FEj final (FEj sobrecarga) e calculada a reserva contrátil. Foi considerado haver reserva contrátil quando que se verificou aumento da FEj ≥ 20% 10 . Os exames ecocardiográficos foram realizados sempre pelo mesmo operador (AG), sendo que o VAE foi retrospetivamente calculado para cada doente e também pelo mesmo operador.…”
Section: Métodosunclassified
“…Foi determinada a FEj final (FEj sobrecarga) e calculada a reserva contrátil. Foi considerado haver reserva contrátil quando que se verificou aumento da FEj ≥ 20% 10 . Os exames ecocardiográficos foram realizados sempre pelo mesmo operador (AG), sendo que o VAE foi retrospetivamente calculado para cada doente e também pelo mesmo operador.…”
Section: Métodosunclassified
“…We need to determine the responses to therapy that lead to a good prognosis in patients with DCM. 37,[41][42][43][44] Exercise testing, in combination with echocardiographic monitoring, may be an attractive and practical method of obtaining accurate information that can aid in the assessment of contractile reserve and prognosis. 38) Observations from previous studies have shown that the capacity for exercise in patients with advanced HF may in fact be more closely related to RV rather than LV performance.…”
Section: )mentioning
confidence: 99%
“…Measures of contractile reserve include SF, EF, posterior wall thickening, wall-motion score index [53,54], change in end-systolic volume [54,55], end-systolic stress and VcFc [56,57], cardiac power [12,56,58], and changes in SI [53,57]. Studies using dobutamine stress echocardiography in adults with nonischemic DCM have demonstrated that measures of contractile reserve may correlate with functional capacity and peak oxygen consumption (VO 2 ) [55,57], as well as prognosis and recovery of LV function [59,60], and survival [54,58,61]. Few studies are published in the pediatric population regarding stress echocardiography and assessment of myocardial contractile reserve, with most studies focused on pediatric patients with anthracycline exposure [62,63].…”
Section: Stress Echocardiographymentioning
confidence: 99%